Lightweight and sustainable materials for automotive applications - Faruk, Omar; Tjong, Jimi; Sain, Mohini, 1956- (CRC Press, 2017)
This book provides critical reviews and the latest research results of various lightweight and sustainable materials in automotive applications. It discusses current applications and future trends of lightweight materials in the automotive area. This is the first book focusing on a broad spectrum of lightweight materials, including metal, plastic, composites, bio-fiber, bio-polymer, carbon fiber, glass fiber, nanomaterials, rubber materials, and foaming materials. The book also includes case studies of commercial lightweight automotive parts from sustainable lightweight materials, providing an invaluable resource to those involved in this in-demand research and commercialization area.